PENDAMPINGAN KADER KESEHATAN DALAM PEMANFAATAN LIMBAH KULIT ARI KEDELAI SEBAGAI BAHAN PANGAN - Indah Sari, Dewi; Fadmawaty, Any; Lindawati, Lindawati (LPPM Universitas Bina Bangsa, 2025)
Skins are one kind of trash generated by the soybean processing industry. Most of the waste that is created is thrown away, not even processed, and thought of as useless items. Compared to tofu dregs, soybean skin has not been used as much and is still only used for animal feed. Therefore, more product development is required to achieve better quality improvements than previously. There is unmanaged garbage and domestic tempeh manufacturing in Banjarsari Village. Residents in the vicinity of the plant have voiced concerns about odors and unattractive vistas. Thus, management must be done, specifically through community service. This project involves helping the neighborhood manage the raw material soybean skin trash